Trace metals in vegetable growing area, western region of central Thailand - Inboonchuay, Tawatchai; Thongjoo, Chaisit; Pongsivapai, Pongpet (Brawijaya University, 2025)
This study investigated the trace metal concentrations in the agricultural area on diverse soil parent materials in the western part of central, Thailand. The soils of 84 areas under vegetable cultivation were sampled. The results revealed that the median concentrations of As, Cd, Cu, Pb, Mo, and Zn are lower than that of the background concentration of heavy metals in Thailand based on the standard of the National Environment Board 2021, whereas the maximum concentrations of As and Cr in some soils were higher than the soil quality standard. Principal component analysis showed that clay, Fe, Mn, Cu, Zn, Ni, Pb, Cr, and As were correlated with clay content in a positive way except for Cd. The general levels of Cu, Fe, Mn, and Zn in edible parts of vegetables are within permissible limits for human food. The median concentration of As, Cd, Ni, and Pb in vegetables is higher than the WHO/FAO maximum permissible limits. Besides, the Fe, Mn, and Zn are most abundant in Chinese flowering cabbage. As, Cd, Ni, and Pb are more abundant in Chinese kale, Chinese cabbage, and cabbage. The maximum concentration of trace metals in some areas is of concern for both food safety and human health.